Being there and being with them: the effects of visibility affordance of online short fitness video on users’ intention to cloud fitness - Chen, Xuewei; Zhu, Yuyi; Xu, Xinyue (Frontiers in Psychology, 2024)
Introduction Cloud fitness is transforming indoor exercise for young people in China. Recent studies have explored the correlation between media use and health-promoting behavior by examining the motivation of individuals and the credibility of influencers. However, the role of media affordance has thus far been largely overlooked. Drawing on the theory of Stimulus-Organism-Response (SOR), the study investigated the indirect effect of visibility affordance on the intention to exercise with fitness influencers in the context of cloud fitness through psychological variables. Methods This paper, based on the online survey data (N = 456), analyses the effect of visibility affordance on the intention to fitness following with influencers. A moderated parallel mediation model was constructed to examine the relationship among related variables. Results The paper draws the following conclusions: (1) Visibility affordance is positively related to the intention to exercise with fitness influencers. (2) Both the sense of social presence and immersion positively mediate the relationship between visibility affordance and the intention to exercise with fitness influencers. (3) The perceived popularity of the influencer positively moderates the relationship between social presence and the intention to exercise with fitness influencers and moderates the mediating role of social presence. Discussion Consequently, this study enhances the existing body of knowledge in exercise behavior and health communication literature, and provides practical implications for short video platform, influencers and individuals in promoting healthier behaviors.